Validation of satellite-derived rainfall estimates against surface-based measurement of Philippine rainfall - Lodangco, Irenea L.Corporal (2005)
The study aims to validate satellite-derived rainfall estimates from two satellite products; namely, Tropical Rainfall Measuring Mission (TRMM) 3B43 and Geostationary Operational Environmental Satellite (GOES)-9 Hydro Estimator (H-E), against Philippine rainfall. The reference values, or the ground-truth data, were obtained fro 59 weather stations of the Philippine Atmospheric, Geophysical and Astronomical Services Administration (PAGASA). A set of validation criteria (correlation coefficient, root mean square error, bias, scatterplot, bias ration and hit rate) was used for quality and skill assessment. It is an attempt to see whether these satellite products capture the complexity of rainfall patterns in a tropical country like the Philippines; and if so, their use to PAGASA to complement forecasting activities and for application in climatological studies on monthly and seasonal scales. The relationships between the casually measured rainfall versus satellite rainfall estimates for both algorithms show a relatively good coincidence. Results of the correlation analysis indicated that the correlation coefficients were significant at 95% probability level for bothh TRMM 3B43 and GOES-9 H-E. The slope of the linear regression line in monthly scatterplots show a slope of lesser steepness than the 1:1 line which means that rainfall estimates from TRMM and GOES-9 were lower than observed. This characteristic is seen for the entire period. TRMM underestimations (negative bias) are more pronounced in areas affected by the northeast and southwest monsoon flow and which coincides with the path of tropical cyclones. Rains associated with the passage of tropical cyclones were underestimated. This pattern was not observed in the rainfall estimation of GOES-9 H-E. Generally, rainfall over the whole country was underestimated by GOES-9 H-E regardless of the prevailing wind flow. Rainfall during the northeast monsoon season is better estimate than southeast monsoon season rainfall. It was manifested in the higher seasonal average of hit rates and correlation coefficients. Likewise, the values for root mean square error and mean bias were lower during the northeast season. For purposes of the study, the gauge rainfall were categorized into <=100m, 101-300 mm, 301-500 mm, and >500 mm, to see the performance of satellite estimates on light and heavy rains. The bias ratio for each categorical rainfall range of GOES-9 H-E gives an impression that light rains were overestimated and heavy rains were underestimated. This trend was also observed in the bias ration of each categorical rainfall range of TRMM during the months of February to May. for the rest of the year, TRMM underestimates rainfall in the <=100 mm range and overestimates it in the 301-500 mm range. The smaller rains are better estimated by TRMM and GOES-9, as can be deduced from the analysis of the hit rates for each categorical rainfall ranges.
"April 2005."
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Rain and rainfall -- Philippines; Rainfall reliability -- Philippines